REAKSI PASAR MODAL INDONESIA TERHADAP PERISTIWA POLITIK - Yosi Stefhani (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2020)
The purpose of this research is to see how the Indonesian capital market reacts to political events. The political event referred to in this study was the election of the President. Capital market reaction can be seen from the presence or absence of differences in abnormal returns before and after the presidential election. The sample in this study companies included in the LQ 45 index during the presidential election period. The presidential election itself was held on April 17, 2019. Observations were made 10 days before the presidential election and 10 days after the presidential election. The data analysis method used is the paired sample t test. The results showed that there were no differences in abnormal returns before and after the election event. The results of this study indicate that the capital market does not react to these political events.